Prehistoric Grinding Tools as Metaphorical Traces of the Past - Lidström Holmberg, Cecilia (Current Swedish Archaeology, 1998)
The predominant interpretation of reciprocating grinding tools is generally couched in terms of low archaeological value, anonymity, simplicity, functionality and daily life of women. It is argued that biased opinions and a low form-variability have conspired to deny grinding tools all but superficial attention. Saddle-shaped grinding tools appear in the archaeological record in middle Sweden at the time of the Mesolithic — Neolithic transition. It is argued that Neolithic grinding tools are products of intentional design. Deliberate depositions in various ritual contexts reinforce the idea of grinding tools as prehistoric metaphors, with functional and symbolic meanings interlinked.